The relationship of the medial roof and the posterior wall of the maxillary sinus to the sphenoid sinus: a radiologic study - Lee,Seung Ju (2017)
Abstract Introduction: The medial maxillary sinus roof is a ridge formed by the superior margin of the maxillary sinus antrostomy. The posterior wall of the maxillary sinus is always included in operative fields. Objective: To perform a radiologic study assessing the utility of the medial maxillary sinus roof and the posterior wall of the maxillary sinus as fixed landmarks for providing a safe route of entry into the sphenoid sinus. Methods: We reviewed 115 consecutive paranasal sinus Computed Tomographic scans (230 sides) of Korean adult patients performed from January 2014 to December 2014. Using the nasal floor as a reference point, the vertical distances to the highest point of the medial maxillary sinus roof, the sphenoid ostium and anterior sphenoid roof and floor were measured. Then the vertical distances from the highest point of the medial maxillary sinus roof to the sphenoid ostium and anterior sphenoid roof and floor were calculated. The coronal distance from the posterior wall of the maxillary sinus to the sphenoid ostium was determined. Results: The average height of the highest point of the medial maxillary sinus roof relative to the nasal floor was measured to be 33.83 ± 3.40 mm. The average vertical distance from the highest point of the medial maxillary sinus roof to the sphenoid ostium and anterior sphenoid roof and floor was 1.79 ± 3.09 mm, 12.02 ± 2.93 mm, and 6.18 ± 2.88 mm respectively. The average coronal distance from the posterior wall of the maxillary sinus to the sphenoid ostium was 0.78 mm. The sphenoid ostium was behind the coronal plane of the posterior wall of the maxillary sinus most frequently in 103 sides (44.4%). It was in the same coronal plane in 68 sides (29.3%) and in front of the plane in 61 sides (26.3%). Conclusions: The medial maxillary sinus roof and the posterior wall of the maxillary sinus can be used as a reliable landmark to localize and to enable a safe entry into the sphenoid sinus.